The Philosophy of Mathematics Education. ([2016]) - Ernest, Paul; Skovsmose, Ole; Bendegem, Jean Paul van, 1953-; Bicudo, Maria Aparecida Viggiani; Miarka, Roger; Kvasz, Ladislav; Moeller, Regina
No abstract available